2009
DOI: 10.1007/s00425-009-1005-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sugar beet chitinase IV on root-associated fungal community of transgenic silver birch in a field trial

Abstract: Heterogenous chitinases have been introduced in many plant species with the aim to increase the resistance of plants to fungal diseases. We studied the effects of the heterologous expression of sugar beet chitinase IV on the intensity of ectomycorrhizal (ECM) colonization and the structure of fungal communities in the field trial of 15 transgenic and 8 wild-type silver birch (Betula pendula Roth) genotypes. Fungal sequences were separated in denaturing gradient gel electrophoresis and identified by sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Nevertheless, these chitinase-expressing silver birches were shown to be more resistant to the leaf spot disease of birch caused by Pyrenopeziza betulicola (Pappinen et al, 2002). Pasonen et al (2009) showed that the mycorrhizal colonization rate of a transformed line of silver birch overexpressing chitinase 3.7 times compared with the control was similar to that of untransformed trees and other wildtype clones. Pasonen et al (2009) showed that the mycorrhizal colonization rate of a transformed line of silver birch overexpressing chitinase 3.7 times compared with the control was similar to that of untransformed trees and other wildtype clones.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, these chitinase-expressing silver birches were shown to be more resistant to the leaf spot disease of birch caused by Pyrenopeziza betulicola (Pappinen et al, 2002). Pasonen et al (2009) showed that the mycorrhizal colonization rate of a transformed line of silver birch overexpressing chitinase 3.7 times compared with the control was similar to that of untransformed trees and other wildtype clones. Pasonen et al (2009) showed that the mycorrhizal colonization rate of a transformed line of silver birch overexpressing chitinase 3.7 times compared with the control was similar to that of untransformed trees and other wildtype clones.…”
Section: Discussionmentioning
confidence: 96%
“…Studies with silver birch looked at overexpression of 4-coumarate:coenzyme A ligase, a lignin biosynthesis gene involved in interactions between roots and soil microorganisms (Seppänen et al 2007). Overexpression of sugar beet chitinase IV in silver birch decreased plant material palpability to insect foragers while increasing resistance to fungal disease (Vihervuori et al 2008;Pasonen et al 2009). American chestnut has been transformed to express the wheat germin-like oxalate oxidase gene in an effort to bolster its resistance to fungal pathogens (Welch et al 2007).…”
Section: Genomic Tools and Genetic Engineering In Hardwood Tree Impromentioning
confidence: 99%
“…The transgenic lines (GM 11 and GM7 not included) were classified into three groups by messenger ribonucleic acid (mRNA) accumulation, high expression (GM4, GM8, GM10, GM12, GM14 and GM15), intermediate expression (GM2, GM3, GM5 and GM9) and low expression (GM1, GM6 and GM13) (Pasonen et al 2004). The total endochitinase activity of selected GM lines (GM2, GM3,GM4, GM8, GM10, GM14 and GM15) and one control line (Ca) was measured by fluorimetric assay for endochitinase from the roots and was shown to be higher (from 1.1-to 3.7-fold) than in the control (Pasonen et al 2009). The number of inserts in the transgenic lines, confirmed by Southern analysis, was estimated to vary from two to four (Pappinen et al 2002).…”
Section: Plant Materialsmentioning
confidence: 99%
“…The in vitro cultures of the seven non-transgenic (wild-type) silver birch clones were initiated from bud meristems and micropropagated by axillary shoot multiplication method in similar growing conditions as the transgenic lines and the two controls. For more detailed description of the clone JR 1/4 and the wild-type clones, see Pasonen et al (2009).…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation